Manifestations of Liver Impairment and the Effects of MH-76, a Non-Quinazoline α1-Adrenoceptor Antagonist, and Prazosin on Liver Tissue in Fructose-Induced Metabolic Syndrome - Monika Kubacka; Barbara Nowak; Monika Zadrożna; Małgorzata Szafarz; Gniewomir Latacz; Henryk Marona; Jacek Sapa; Szczepan Mogilski; Marek Bednarski; Magdalena Kotańska (Metabolites, 2023)
Excessive fructose consumption may lead to metabolic syndrome, metabolic dysfunction-associated fatty liver disease (MAFLD) and hypertension. α1-adrenoceptors antagonists are antihypertensive agents that exert mild beneficial effects on the metabolic profile in hypertensive patients. However, they are no longer used as a first-line therapy for hypertension based on Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attack Trial (ALLHAT) outcomes. Later studies have shown that quinazoline-based α1-adrenolytics (prazosin, doxazosin) induce apoptosis; however, this effect was independent of α1-adrenoceptor blockade and was associated with the presence of quinazoline moiety. Recent studies showed that α1-adrenoceptors antagonists may reduce mortality in COVID-19 patients due to anti-inflammatory properties. MH-76 (1-[3-(2,6-dimethylphenoxy)propyl]-4-(2-methoxyphenyl)piperazine hydrochloride)) is a non-quinazoline α1-adrenoceptor antagonist which, in fructose-fed rats, exerted anti-inflammatory, antihypertensive properties and reduced insulin resistance and visceral adiposity. In this study, we aimed to evaluate the effect of fructose consumption and treatment with α1-adrenoceptor antagonists of different classes (MH-76 and prazosin) on liver tissue of fructose-fed rats. Livers were collected from four groups (Control, Fructose, Fructose + MH-76 and Fructose + Prazosin) and subjected to biochemical and histopathological studies. Both α1-adrenolytics reduced macrovesicular steatosis and triglycerides content of liver tissue and improved its antioxidant capacity. Treatment with MH-76, contrary to prazosin, reduced leucocytes infiltration as well as decreased elevated IL-6 and leptin concentrations. Moreover, the MH-76 hepatotoxicity in hepatoma HepG2 cells was less than that of prazosin. The use of α1-adrenolytics with anti-inflammatory properties may be an interesting option for treatment of hypertension with metabolic complications.